Parental Involvement on Students’ Achievement During Lockdown - Saikhoni Saikhoni; Yulianto Yulianto (Peneliti.net, 2021)
The pandemic of Covid-19 has changed how education works in the current time. A student’s learning development has always been placed on the responsibility of the campus. However, during the pandemic, parental involvement has become vital in the world of education. The involvement of just a few parents may influence the quality of instruction in a classroom or at home and, thereby, influence the academic development of many students in Indonesia. This research aims to determine parental involvement students’ education in Pringsewu, Lampung. Besides, it was also to help lecturer and administrators to provide activities that encourage parents to participate in students’ activities at home. The data was collected via questionnaires and phone interviews. The participants involved were 10 parents and 5 lecturers from Muhammadiyah University, Pringsewu, Lampung. Based on the finding of this research, parental involvement has had a big influence in student’s academic achievement. Although the importance of parental involvement is widely acknowledged in the educational society, most of parents showed that many parents still do not get involve effectively in their student’s education whether in campus or at home. In conclusion, parental involvement is very essential and will help to enhance student’s social relationships and promote a sense of self-esteem and self-efficacy